Placenta accreta spectrum disorders clinical practice guidelines: A systematic review. Issue 5 (16th February 2023) - Capannolo, Giulia; D'Amico, Alice; Alameddine, Sara; Di Girolamo, Raffaella; Khalil, Asma; Calì, Giuseppe; Trish, Ilan T.; Coutinho, Conrado M.; Herrera, Mauricio; Liberati, Marco; Lucidi, Alessandro; Palacios‐Jaraquemada, Jose; et al.
Abstract: Objectives: To objectively assess the quality of the published clinical practice guidelines (CPGs) on the management of pregnancies complicated by placenta accreta spectrum (PAS)disorders. Methods: MEDLINE, Embase, Scopus, and ISI Web of Science databases were searched. The following aspects related to the management of pregnancies with suspected PAS disorders were evaluated: risk factors for PAS, prenatal diagnosis, role of interventional radiology and ureteral stenting, and optimal surgical management. The assessment of risk of bias and quality assessment of the CPGs were performed using the (AGREE II) tool (Brouwers et al., 2010). To define a CPG as of good quality we adopted a cut‐off score >60%. Results: Nine CPGs were included. Specific risk factors for referral were assessed by 44.4% (4/9) of CPGs, mainly consisting in the presence of placenta previa and a prior cesarean delivery or uterine surgery. About 55.6% of CPGs (5/9) suggested ultrasound assessment of women with risk factors for PAS in the second and third trimester of pregnancy and 33.3% (3/9) recommended magnetic resonance imaging (MRI); 88.9% (8/9) of CPGs recommended cesarean delivery at 34–37 weeks of gestation. There was not generally consensus on the use of interventional radiology and ureteral stenting before surgery for PAS. Finally, hysterectomy was the recommend surgical approach by 77.8% (7/9) of the included CPGs. Conclusion: Most of the published CPGs on PAS are generally of good quality. There was general agreement among the different CPGs on PAS as a regard as risk stratification, timing at diagnosis and delivery but not on the indication for MRI, use of interventional radiology and ureteral stenting.